A Study of Facial Index among Patients Visiting Orthodontics Department at Nishtar Institute of Dentistry, Multan - Umal Asim, Zubair Hassan Awaisi, Zubair Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine mutifarious facial types of the patients and also determine gender dimorphism. Study Design: Case-control study Place and Duration of Study: Department of Orthodontics, Nishtar Institute of Dentistry Multan from 1st December 2020 to 30th June 2021. Methodology: One hundred patients were included in the study having 50 females and 50 males. The patients were asked to sit up straight with eyes focused on a distant point at eye level. The Bertillon caliper was utilized to measure the morphological face height as a vertical distance from nasion (n) to gnathion (gn). The facial width was estimated transversely as a distance between the right and left zygion (zy) points employing the same caliper. Results: According to the Banister classification the most common facial type was found to be hypereuriprosopic (52%) which symbolizes very short and broad faces. Euriprosopics were 28% and mesoprosopics were 15%.Pertaining to gender dimorphism both males and females were predominantly hypereuriprosopic (31% in females and 21% in males). The second common face type reported was euriprosopicin males (20%) and for females it was mesoprosopic (10%). Conclusion: Facial phenotype is strongly influenced by genetic and environmental factors. The most common facial type was hypereuriprosopic followed by euriprosopic. Keywords: Facial index, Facial type, Gender dimorphism